Pengaruh Penyuluhan Kesehatan Terhadap Pemahaman Madamat Tentang Slogan “Isi Piringku” Sebagai Upaya Pencegahan Penyakit Tidak Menular: English - Najie, Ilyu Ainun; Nurhuda, Yusa Amin; Faramarisa, Fara Fayo; Suriyeni, Deni; Insan, Wachidah Nuril (Yayasan Jompa Research and Development, 2025)
Indonesia is currently undergoing a transition in lifestyle, dietary patterns, and demographics, which has led to a continuous increase in non-communicable diseases (NCDs). The main risk factor for NCDs is an unbalanced diet. My plate is a slogan for balanced nutrition, which, when applied in daily life, can help promote healthy eating habits among families and communities. Health education has great potential as an effective medium of education, aiming to determine the effect of health counseling on Madamat’s understanding of the “My Plate” slogan as a preventive effort against non-communicable diseases in families. It is also expected to encourage Madamat to adopt healthier dietary behaviors within their families as an early preventive measure against NCDs. This study used a quantitative method with a pre-experimental design, consisting of one large group with a pre-test and post-test pattern. The group included Madamat, namely the wives of lecturers and academic staff at UNIDA, totaling 30 participants. The research results were analyzed using frequency distribution with univariate and bivariate analysis, producing a significance value (p=0.000), indicating that health counseling had an effect on improving Madamat’s understanding of the “My Plate” slogan as a preventive measure against non-communicable diseases. The conclusion of this study is that there was a positive effect and an improvement in understanding as a result of health counseling, which contributed to enhancing Madamat’s knowledge regarding the prevention of non-communicable diseases through the application of “My Plate.”